2005
DOI: 10.1378/chest.127.6.1960
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Improvement After Lung Volume Reduction Surgery for Severe Emphysema

Abstract: Conclusions: Lung volume reduction surgery significantly improves BMD compared to respiratory rehabilitation therapy, even in patients requiring oral steroids. The increase in BMD correlates with RV, DLCO, and fat-free mass, suggesting that the restoration of respiratory dynamics, gas exchange, and nutritional status induces improvement in bone metabolism and mineral content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
5
34
1
1
Order By: Relevance
“…It would be compelling to study the effect on bone density of interventions aiming at increasing daily physical activity. In fact, it has already been shown that patients with COPD present an improvement in bone mineral density after lung volume reduction surgery, which has been ascribed to an increase in physical activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…It would be compelling to study the effect on bone density of interventions aiming at increasing daily physical activity. In fact, it has already been shown that patients with COPD present an improvement in bone mineral density after lung volume reduction surgery, which has been ascribed to an increase in physical activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…All these changes appeared correlated with the surgical reduction of residual volume [12,[25][26][27].…”
Section: Commentmentioning
confidence: 72%
“…Resting energy expenditure and metabolism were evaluated for the first time by using a calorimetric chamber with indirect methods. In addition, nutrional status was more accurately evaluated in comparison with our previous studies [26,27] by using dual-energy X-ray absorptiometry for body composition, both fat and fat-free mass.…”
Section: Commentmentioning
confidence: 99%
“…In spite of oral steroid therapy, bone density improved after the surgery, which was maintained after surgery in about 50% of patients, suggesting association of emphysema and osteoporosis. 28 Low BMI has shown to be predictive of osteoporosis among COPD patients.…”
Section: Discussionmentioning
confidence: 99%